2014
DOI: 10.1369/0022155414523022
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Phospho-AKT, Phospho-mTOR, Phospho-MAPK and EGFR in Non-small Cell Lung Cancer

Abstract: Activation of numerous pathways has been documented in non-small cell lung cancer (NSCLC). Epidermal growth factor receptor (EGFR) has emerged as a common therapeutic target. The mitogen-activated protein kinase (MAPK) and AKT signaling pathways are downstream of EGFR and deregulated via genetic and epigenetic mechanisms in many human cancers. We evaluated selected markers in the EGFR pathway with reference to outcome. Tissues from 220 cases of NSCLC patients presented in a tissue microarray were assayed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Given the substantial correlation in expression between PLK1 and ECT2 and the fact that PLK1 has been demonstrated to phosphorylate ECT2 in vitro (Niiya et al, 2006), we evaluated the combination of the two biomarkers to predict outcome. Based on prior examples of ratiometric combination of related biomarkers (Chung et al, 2009; Kitano et al, 2014), we generated a PLK1/ECT2 ratio from the TMA scores, and performed survival analysis (Figure 6G), which demonstrated that the PLK1/ECT2 ratio was robust to discriminate outcomes. To determine whether the combination of PLK1 and ECT2 expression was a universal predictor of outcome, we assessed high/low mRNA combination groups based on the median expression of the two genes in various cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the substantial correlation in expression between PLK1 and ECT2 and the fact that PLK1 has been demonstrated to phosphorylate ECT2 in vitro (Niiya et al, 2006), we evaluated the combination of the two biomarkers to predict outcome. Based on prior examples of ratiometric combination of related biomarkers (Chung et al, 2009; Kitano et al, 2014), we generated a PLK1/ECT2 ratio from the TMA scores, and performed survival analysis (Figure 6G), which demonstrated that the PLK1/ECT2 ratio was robust to discriminate outcomes. To determine whether the combination of PLK1 and ECT2 expression was a universal predictor of outcome, we assessed high/low mRNA combination groups based on the median expression of the two genes in various cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Normal tissue TMAs failed to demonstrate staining of tumor markers. ECT2/PLK1 ratios were calculated from raw data, and cut points were determined as ECT2/PLK1 ratio ≤1 for the low and >1 for the high group, similar to that previously described (Kitano et al, 2014), and plotted as Kaplan-Meier plots. High or low mRNA levels of PLK1 and ECT2 were determined using a median score.…”
Section: Star Methodsmentioning
confidence: 99%
“…9B and 10). These include: Akt and MAPK signaling pathways which are involved in mediating cell growth and proliferation, respectively [39, 40]; FAK, along with other ErbB signaling molecules, which participate in angiogenesis, cell motility, adhesion, and organogenesis [40]. Results of this study also showed the ability of 1 to inhibit Brk tyrosine kinase phosphorylation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 80%
“…As a multifactorial cancer, NSCLC can be triggered by many risk factors including tobacco smoking, second-hand or passive smoking, diet, excess alcohol consumption, air pollution, occupational exposure and genetic predisposition (6,7). A combination of radiotherapy and chemotherapy, along with surgical treatment, is the current treatment standard to achieve local tumor control and prolonged survival (8,9). Notably, previous evidence has shown that the long-term survival rates of lung cancer patients remain low and the 5-year overall survival rate of NSCLC is ~15% in the US and <10% in China (1,10,11).…”
Section: Introductionmentioning
confidence: 99%